Opportunity of Using Feather Meal for Ruminant Feed Stuff - Adiati, Umi; Puastuti, Wisri; Mathius, I W (Indonesian Bulletin of Animal and Veterinary Sciences, 2004)
Feather, a waste product of chicken is a potencial protein source for animal feeds. The average production of feather is 6% of the life weight of the chicken. Broiler population in Indonesia in 2003 was 917,707,000; for DKI area was 1,360,000 while for West Java was 308,021,118. Research results indicate that chicken were slaughtered at 35 day of age with the range of body weight of 1 to 2.2 kg. The number of broiler slughtered every month in Jakarta is 4,679,500 head, resulted in feather of 350 ton/month while for Bogor area the number of slaughtered broiler is 1,255,000 head/month, produce feather of 135 ton/month. Feather meal can be used as protein source in ruminant feed as much as 40%. Key words: Feather meal, crude protein, ruminant feed stuff